2019
DOI: 10.26444/aaem/105436
|View full text |Cite
|
Sign up to set email alerts
|

Peritraumatic distress among emergency medical system employees: A proposed cut-off for the Peritraumatic Distress Inventory

Abstract: Introduction. Emergency medical system (EMS) workers are exposed to traumatic events that may lead to posttraumatic stress disorder (PTSD). Objectives. The purpose of this study was to explore and discuss the relationship between peritraumatic distress (PD) and elevated posttraumatic stress symptoms (PTSS) in EMS employees. Material and methods. A cross-sectional study including 100 EMS employees was conducted. Demographic and occupational data were collected for each subject. The Polish version of the Impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Previous research found that individuals were more likely to exhibit the event‐associated stress symptom if they perceived a greater threat of the life event (Rybojad et al., 2019). In this study, it was found that the increased COVID‐19 related stress symptom was linked to psychological distress among the frontline nurses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research found that individuals were more likely to exhibit the event‐associated stress symptom if they perceived a greater threat of the life event (Rybojad et al., 2019). In this study, it was found that the increased COVID‐19 related stress symptom was linked to psychological distress among the frontline nurses.…”
Section: Discussionmentioning
confidence: 98%
“…Due to the dynamic environment, ED nurses usually perceived higher level of work stress. Previous study reported that 7%–10% of emergency service personnel experienced distress and post‐traumatic stress disorder (Rybojad, Aftyka, & Milanowska, 2019). During the current outbreak of COVID‐19, ED nurses had to face an unpredictable number of potential or suspected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological impact of COVID-19 was measured using the Impact of Event Scale-Revised (IES-R). The IES-R was validated in Polish and Chinese population for determining the extent of psychological impact after exposure to a recent event that might threaten survival (i.e., the COVID-19 pandemic) (25)(26)(27). This 22-item questionnaire which is composed of three subscales, aims to measure the mean avoidance, intrusion, and hyperarousal (28).…”
Section: Discussionmentioning
confidence: 99%
“…We translated the questionnaire in Italian, adapted it to the original English version, and then tested it in a large sample of HCWs exposed to multiple patient’s death and other life-threatening events, such as the high-risk exposure to the COVID-19 infection during the acute phase of the pandemic in Italy. Previous studies on the Polish version of the PDI demonstrated that samples of HCWs could be used for the validation of the tool and highlighted the utility of such instrument in this population (Rybojad & Aftyka, 2018 ; Rybojad et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent prospective data suggest that peritraumatic distress is a stronger predictor of the development of PTSD symptoms than peritraumatic dissociation (Bui et al., 2010 ). Due to its utility in clinical and research setting, the tool was validated in various languages (Jehel, Brunet, Paterniti, & Guelfi, 2005 ; Kianpoor et al, 2016 ; Nishi et al, 2009 ; Rybojad & Aftyka, 2018 ) and in particular populations, such as children (Bui et al, 2011 ), elderly (Bui et al, 2010 ; Brunet et al, 2013 ), caregivers (Rybojad, Aftyka, & Samardakiewicz, 2018 ) or HCWs, (Rybojad, Aftyka, & Milanowska, 2019 ). To the best of our knowledge, to date there are no official validations of the PDI in Italian.…”
Section: Introductionmentioning
confidence: 99%